Perbedaan Nilai Indeks Eritrosit Pada Sampel Darah Vena Dengan Pengambilan Posisi Duduk Dan Posisi Berbaring - Juraijin, Denny; Yunita, Ade; Nurhidayanti, Nurhidayanti (Indobiosains, 2024)
The erythrocyte index or Mean Cospuscular Value is an average value that can provide information about the average erythrocyte and the amount of hemoglobin per-erythrocyte. The erythrocyte index consists of Mean Corpuscular Volume (MCV) or the average volume of an erythrocyte, Mean Corpusculara Hemoglobin (MCH) or the amount of hemoglobin per-erythrocyte, Mean Corpuscular Hemoglobin Concentration (MCHC) or the concentration of hemoglobin obtained per-erythrocyte. Erythrocyte index examination is more specifically used to determine what type of anemia is suffered by someone who experiences it. This study aims to determine the difference in the results of the examination of erythrocyte index values in venous blood sampling by taking sitting and lying positions. This research method is Crossectional, research conducted at Bunda Hospital Palembang. The population taken was female students of the S.Tr study program. Medical Laboratory Technology Muhammadiyah Palembang, Samples used in this study amounted to 31 samples using Purposive Sampling. The study obtained the results of MCV sitting position 84.88 and lying position 84.34 fl, MCH obtained an average value in sitting position 28.09 and lying position 28.05 pg / cell and MCHC examination obtained an average value in sitting position 33.05 and lying position 33.22 g / dl which means there are differences in erythrocyte index examination in venous blood sampling with sitting position and lying position. It can be concluded that venous blood sampling in the sitting position is not recommended for erythrocyte index examination, because the examination results are different in the sitting position.